Administration of high dose intravitreal melatonin degenerates retinal cells in guinea pigs - Yilmaz, Turgut; Naziro?lu, Mustafa; Çelebi, Serdal; Özercan, H. Ibrahim; Kükner, A. Şahap (My University, 2004)
The purpose of this study was to investigate the influence of intravitreally injected different doses of melatonin on retinal morphology. The right eyes of 35 male albino guinea pigs were used. The animals were classified randomly into five groups in equal numbers. First group was used as control and received intravitreal injection of placebo. Groups 2, 3, 4 and 5 received intravitreally injections of melatonin at 50, 100, 150 and 200 ?g/body weight (BW) each, respectively. The animals were sacrificed 15 days after the injections. The eyes were enucleated and processed for light microscopic evaluation.Intravitreal injection of melatonin at doses ranging from 50 to 150 ?g did not induce morphological changes, although a higher thickness of the inner plexiform layer (IPL) was found in Group 5 compared to other groups (p < 0.05). The mean retinal ganglion cell (RGC) counts were found to be lower in Group 5 compared to other groups (p < 0.05).Our findings indicate that intravitreal injection of melatonin at doses ranging from 50 to 150 ?g/BW does not induce morphological changes. The dose of 200 ?g/BW produced significant damage including retinal ganglion cell loss and formation of retinal edema. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: Histology; Intravitreal injection; Melatonin; Retina